Prevalence and factors associated with undiagnosed type 2 diabetes among adults in Iraq: analysis of cross-sectional data from the 2015 STEPS survey - Pengpid S. (2023)
Objective The purpose of the study was to assess the prevalence and correlates of undiagnosed type 2 diabetes (UT2D) among adults (aged 18 years and older) in Iraq. Design Cross-sectional, population-based study. Setting Nationally representative sample of general community-dwelling adult population in Iraq from the 2015 Iraq STEPS survey. Participants The sample included 3853 adults (mean age 41.8 years, SD=15.8), with complete fasting blood glucose values, from the 2015 Iraq STEPS survey. Outcome measures Data collection included: (1) social and behavioural information, (2) physical parameters and blood pressure measurements and (3) biochemical measurements. UT2D was classified as not being diagnosed with T2D and fasting plasma glucose level ≥126 mg/dL. Multivariable multinomial and logistic regression was used to identify factors associated with UT2D. Results The prevalence of UT2D was 8.1% and the prevalence of diagnosed T2D (DT2D) was 8.9%. Participants aged 50 years and older (adjusted relative risk ratio (ARRR): 2.11, 95% CI 1.30 to 3.43) and those with high cholesterol (ARRR: 1.54, 95% CI 1.05 to 2.24) had a higher risk of UT2D. Older age (≥50 years) (ARRR: 17.90, 95% CI 8.42 to 38.06), receipt of healthcare advice (ARRR: 2.15, 95% CI 1.56 to 2.96), history of cholesterol testing (ARRR: 2.17, 95% CI 1.58 to 2.99), stroke or heart attack (ARRR: 1.81, 95% CI 1.13 to 2.92), and high cholesterol (ARRR: 1.55, 95% CI 1.17 to 2.06) were positively associated with DT2D, and high physical activity (ARRR: 0.57, 95% CI 0.38 to 0.84) was negatively associated with DT2D. Higher than primary education (adjusted OR (AOR): 2.02, 95% CI 1.21 to 3.37) was positively associated with UT2D versus DT2D, while older age (≥50 years) (AOR: 0.12, 95% CI 0.06 to 0.25), healthcare advice (AOR: 0.45, 95% CI 0.29 to 0.70), and history of cholesterol screening (AOR: 0.37, 95% CI 0.24 to 0.58) were inversely associated with UT2D versus DT2D. Conclusion Almost one in ten adults in Iraq had UT2D, and various associated factors were identified that could be useful in planning interventions.